Prediction of Aryl Hydrocarbon Receptor-Mediated Enzyme Induction of Drugs and Chemicals by mRNA Quantification - Frötschl, Roland; Chichmanov, Lubomir; Kleeberg, Ullrich; Hildebrandt, Alfred G; Roots, Ivar; Brockmöller, Jürgen (Chemical research in toxicology, 1998)
Enzyme-specific testing for drug interactions by in vitro techniques has become a routine practice in drug development. With many drugs, enzyme induction has similar importance for the prediction of drug−drug interactions. We developed a method for recognizing enzyme induction mediated via the aryl hydrocarbon receptor. This type of induction may be clinically important since experimental data suggest a higher rate of toxification in induced subjects. Twenty-four drugs and environmental chemicals, selected as prototype inducers or being chemically related to known inducers, including HIV protease inhibitors nelfinavir, saquinavir, ritonavir, and indinavir, were tested for their potency to induce cytochrome P450 1A1 mRNA in human Hela cell cultures by a quantitative reverse transcriptase polymerase chain reaction. Known prototype inducers such as β-naphthoflavone and 3-methylcholanthrene exhibited the highest inducing potency quantified with an I max value (maximal induction of cytochrome P450 1A1 mRNA synthesis) of 5.48 and 10.7 × 106 mRNA molecules per 150 ng of total RNA, respectively. The enzyme-inducing efficacy of some compounds such as resveratrol (2.92 × 106) and the protease inhibitors was not much lower (2.23−3.08 × 106). All compounds that were structurally similar to benzimidazoles exhibited some extent of enzyme induction; e.g., I max values were 0.86 × 106, 0.20 × 106, and 0.14 × 106 for omeprazole, lansoprazole, and losartan, respectively. To predict the clinical relevance of these inducing effects, the concentration at half-maximal induction I M was estimated; the plasma concentrations of these drug substances were within 1 order of magnitude of the I M values, upon usual dosage. In conclusion, cytochrome P450 1A1 enzyme induction by drugs is a common phenomenon, though there is a great range in the inducing efficacy. In vitro prediction of enzyme induction may be useful for explaining or foreseeing drug interactions, drug side effects, or toxicity by xenobiotics.